2014
DOI: 10.5326/jaaha-ms-5972
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous Cystitis and Pyelonephritis in a Nondiabetic Dog and a Diabetic CatS

Abstract: Emphysematous cystitis (EC) and emphysematous pyelonephritis (EPN) are the result of infection of the urinary bladder and kidneys by gas-producing microorganisms. Those infections are most often reported in diabetic patients and rarely occur concurrently. This article describes two cases of concurrent EC and EPN, one in a nondiabetic dog and the other in a diabetic cat. The use of diagnostic imaging is necessary in the diagnosis of emphysematous infections. Both radiography and ultrasonography were used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…This facultative anaerobic microorganism has gas‐producing properties . It can induce emphysematous inflammation, as in cystitis, particularly in diabetic but also in nondiabetic dogs . Interestingly, it is the main pathogen in most nondiabetic emphysematous cystitis cases reported in dogs and has been reported in one cat .…”
Section: Discussionmentioning
confidence: 99%
“…This facultative anaerobic microorganism has gas‐producing properties . It can induce emphysematous inflammation, as in cystitis, particularly in diabetic but also in nondiabetic dogs . Interestingly, it is the main pathogen in most nondiabetic emphysematous cystitis cases reported in dogs and has been reported in one cat .…”
Section: Discussionmentioning
confidence: 99%
“…EC has been diagnosed in patients with primary renal glycosuria (Fanconi’s syndrome), urinary tract obstruction, chronic urinary tract infections, neurogenic bladder dysfunction, morphologic abnormalities and immunosuppression 4,811…”
Section: Prevalence and Impactmentioning
confidence: 99%
“…In humans, cases of EC are reported approximately twice as often in women as in men; in general, middle-aged, diabetic women appear to be at a significantly higher risk for disease 1. While female dogs and cats are at increased risk of developing an UTI, and several studies demonstrated an increased risk with increasing age, for EC no gender nor age predisposition has been reported in dogs or cats until now 8,14…”
Section: Prevalence and Impactmentioning
confidence: 99%
See 2 more Smart Citations